Emergence of human West Nile Virus infection among pediatric population in Madhya Pradesh, India. Issue 3 (15th October 2018) - Tandel, Kundan; Sharma, Shashi; Dash, Paban Kumar; Shukla, Jyoti; Parida, Manmohan
Abstract : Human infections caused by West Nile virus (WNV) mostly remain subclinical and self‐limited. However, nearly 20% infected people suffer from febrile illness and very few of them (<1%) may get neuroinvasive illness. Mortality has been reported among children. India somehow has reported very less number of WNV cases in the past. We collected cerebrospinal fluid (CSF) samples from 75 pediatric age group patients clinically suffering from acute encephalitis syndrome. Three of these samples were positive by reverse transcriptase polymerase chain reaction using pan flavivirus primers. On sequencing of the 212 bp long–amplified fragment, it was found to be WNV belonging to lineage 1. This is probably the first report of WNV causing encephalitis from this central part of India. Abstract : This manuscript highlights the importance of widespread surveillance for this virus as a cause of encephalitis. It also highlights the importance of using molecular tests for the screening purpose.